Pengaruh Pengetahuan dan Reputasi terhadap Kepercayaan dan Intensi Berkurban di Masjid dengan Moderasi Religiusitas - Oktafia, Vita; Sutarso, Yudi (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This research analyze the trust and intention of the community to kurban at the mosque. This research uses a quantitative approach with a purposive sampling technique and uses the SEMPLS test. This study was conducted to determine the relationship between knowledge and reputation variables on trust and intensity of kurban in mosques with religiosity as a moderating variable. The data used is primary data in the form of a questionnaire with a population obtained from one hundred and one respondents who are Muslims. The results of this study show public knowledge and mosque reputation do not affect the intensity of people's kurban at the mosque. However, knowledge and reputation affect the increase in public trust in the mosque. And then religiosity as a moderating variable in this study does not affect the intensity of the community to kurban at the mosque.